2021
DOI: 10.7575/aiac.ijkss.v.9n.3p52
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 Effects on University Student’s Health Behaviours: The FRESH Study

Abstract: Background: The imposed stay-at-home restrictions with the coronavirus (COVID-19) pandemic disrupted daily routines and impacted some population groups more than others. One such group included university students who were forced to adapt to online classes reducing face to face interactions. The uncertainty associated with this change may have created a sense of anxiety and fear towards the virus. Objective: The objective of this study was to measure the level of fear associated with COVID-19 in Canadian under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“… Turkey Europe Medical 47.39 Collectivism Elsayed and Ghazi, 2021 275 6.5 Egypt Middle East Healthcare students N.A. Collectivism Ghaderi et al, 2021 457 4.5 Iran Middle East General population 37.86 Collectivism Grande and Doyle-Baker, 2021 680 13.5 Canada North America University students 23 Individualism Green et al, 2021 608 9 Pakistan Asia University students 24.76 Collectivism Gélinas et al, 2021 1517 N.A. Canada North America Hospital staff 41.11 Individualism Jafari-Oori et al, 2021 350 N.A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Turkey Europe Medical 47.39 Collectivism Elsayed and Ghazi, 2021 275 6.5 Egypt Middle East Healthcare students N.A. Collectivism Ghaderi et al, 2021 457 4.5 Iran Middle East General population 37.86 Collectivism Grande and Doyle-Baker, 2021 680 13.5 Canada North America University students 23 Individualism Green et al, 2021 608 9 Pakistan Asia University students 24.76 Collectivism Gélinas et al, 2021 1517 N.A. Canada North America Hospital staff 41.11 Individualism Jafari-Oori et al, 2021 350 N.A.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, continent was added in the meta-analysis as a potential moderator to assess the moderating effect of different countries. In most studies conducted in North America, females had higher levels of COVID-19 related fear and anxiety than males (Camacho et al, 2020; Grande and Doyle-Baker, 2021 ; García-Reyna et al, 2021 ; Gélinas et al, 2021 ; Landa-Blanco et al, 2021 ; Lee et al, 2020 ; Pérez-Fuentes et al, 2020 ; Ojalehto et al, 2021 ). In addition, studies conducted in Europe, female's COVID-19 related fear and anxiety levels were higher ( Bakioğlu et al, 2020 ; Kaçoğlu et al, 2021 ; Morales-Rodríguez, 2021 ; Orrù et al, 2021 ; Tsipropoulou et al, 2020 ; Ypsilanti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Grande and Doye Baker showed that Canadian students demonstrated a moderate level of fear associated with the COVID-19 pandemic, and those with a high level of fear reported more negative choices concerning health behaviours. These findings emphasised that continuous restrictions during the COVID-19 pandemic have a negative impact on students’ health behaviours [ 41 ]. Similar observations were made in the study by Savage et al that the COVID-19 pandemic has a negative impact on the mental health and physical exercise of British university students [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is important to consider that the fear of COVID-19 has had an impact on the lifestyle habits of university students, such as resorting to increased alcohol or tobacco consumption as coping responses to the stressors associated with the COVID-19 pandemic ( 43 ), adopting less healthy dietary practices ( 44 ), and exhibiting a low level of physical activity ( 45 ).…”
Section: Introductionmentioning
confidence: 99%